Coalbed methane potential in Kalimantan-Indonesia: Geological condition, membrane technology, environmental and economic challenges - Fikri, Hafidz Noor; Elma, Muthia; Rahma, Aulia; Azwar, Prayudhi; Handoko, Heryanto; Rahmi, Resti Nisaidha (Brawijaya University, 2026)
Kalimantan has extensive Neogene coal reserves, making it an area with great potential for coalbed methane (CBM). After decades of preliminary investigations and studies, coalbed methane production has not yet reached the desired level. This indicates a complex interaction among geological, techno-economic, and environmental challenges. This study provides a literature review on the CBM potential in Kalimantan. A comprehensive literature study was conducted on the coalbed methane system in Kalimantan. The key parameters synthesized are the geological conditions of coal in the form of thermal maturity, gas composition, adsorption characteristics, and permeability, followed by the environmental impact and economic feasibility when applied. It appears that the greatest potential for CBM lies in the Kutai, Barito, and Tarakan basins. The reported Kalimantan coal ranks are primarily sub-bituminous to high-volatile bituminous (Ro = 0.4%-0.7%). Gas storage capacity significantly, ranging from 44 to 410 scf/ton (1.5-9.0 m³/ton). However, CBM application is hampered by poor reservoir permeability (often <5 mD) and undersaturated deposit conditions. Studies have shown that high development costs, long drying times, and unfavorable fiscal conditions have made most CBM projects uneconomical at current domestic gas prices. This review reconfirms that Kalimantan holds significant CBM resources. However, the financial viability of CBM projects depends on the ability to address significant technical barriers and requires financial incentives due to the high risks and substantial long-term investments involved.